STRATEGI EXPERIENTIAL MARKETING DAN KUALITAS PELAYANAN DALAM MENJELASKAN KEPUASAN DAN LOYALITAS NASABAH PADA BANK SYARIAH MANDIRI SEMARANG - Arif Afendi (SEGMEN Jurnal Manajemen dan Bisnis, 2021)
The purpose of this research is to test the effect of experiental marketing and service quality on customer satisfaction and customer loyalty. The type of research used is quantitative research using the Structural Equation Model (SEM) method. The data in this study was primary data with 100 respondents of mandiri syaria bank (BSM) Semarang. The results of this study show that there is a positive and significant effect of experiental marketing and servic quality  on customer satisfaction. The effect of the service quality on customer loyalty is positive and significant. The effect of customer loyalty is positive and significant  while the effect of experiental marketing to customer loyalty is positive but not significant.Keywords: experiental marketing, service quality, customer loyalty, customer satisfaction